The Effects of LiO Doping on the Surface and Catalytic Properties of CuO/AlO Solids - Gamil A. El-Shobaky; Farouk M. Radwan; Abd. El-Mohsen Turky; Ayman Abd. El-Moemen (Adsorption Science & Technology)
The effects of doping CuO/Al 2 O 3 solids with Li 2 O on their surface and catalytic properties were investigated using nitrogen adsorption at −196°C, the decomposition of H 2 O 2 at 20–40°C and the oxidation of CO by O 2 at 175°C. The pure solids were prepared by wet impregnation of finely powdered solid Al(OH) 3 which had been precalcined at 400°C; the resulting material was then dried and calcined at 500°C with copper nitrate dissolved in the least amount of distilled water. The amount of copper oxide in such solids was fixed at 13.5 wt% while the amounts of Li 2 O added varied between 0.19 wt% and 3.80 wt%. The results obtained showed that such Li 2 O doping enhanced the crystallization of the CuO phase to an extent proportional to the amount of dopant added and increased the concentration of surface OH groups. This treatment led to a progressive small increase in the BET surface areas (S BET ) of the treated solids, which attained a maximum limit at 0.76 wt% Li 2 O but decreased upon increasing the dopant concentration above this limit. The addition of 0.76 wt% Li 2 O effected an increase of 14.6% in the S BET values of the treated solids while the addition of 3.80 wt% Li 2 O led to a corresponding decrease of 38.5% in this value. Doping with Li 2 O resulted in a progressive decrease in the catalytic activity of the solids towards CO oxidation by O 2 while the presence of 3.80 wt% Li 2 O effected a decrease of 72.5% in the value of the reaction rate constant measured at 175°C. In contrast, such treatment of CuO/Al 2 O 3 solids with Li 2 O brought about a progressive increase in their catalytic activity towards H 2 O 2 decomposition, which reached a maximum limit in the presence of 1.90 wt% Li 2 O and then decreased when the amount of Li 2 O added was increased above this limit, falling to values which were smaller than those measured for the pure catalyst samples. The doping process did not modify the activation energy of the catalyzed H 2 O 2 reaction but modified the concentration of the catalytically active constituent present in the system.